4х - 3 = -х + 12 9 - 7у = 25 - 3у
4х + х = 12 + 3 -7у + 3у = 25 - 9
5х = 15 -4у = 16
х = 15 : 5 у = 16 : (-4)
х = 3 у = -4
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
-2n = 5,6n 2(11 - 4а) = 3 - (5а + 2)
-2n - 5,6n = 0 22 - 8а = 3 - 5а - 2
-7,6n = 0 -8а + 5а = 1 - 22
n = 0 : (-7,6) -3а = -21
n = 0 а = -21 : (-3)
а = 7
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3(-5 + с) - 2(с - 4) = 2 - 7(с - 1) 2,4b - 1,5 = 0,2 - 0,6(3 - 4b)
-15 + 3с - 2с + 8 = 2 - 7с + 7 2,4b - 1,5 = 0,2 - 1,8 + 2,4b
с + 7с = 9 + 7 2,4b - 2,4b = -1,6 + 1,5
8с = 16 0b = -0,1
с = 16 : 8 b - нет решений, так как
с = 2 на 0 делить нельзя! (∅)
2) в(71,4-70,2)=1,2в
3) 2,5с+3,6с+1,2+5=с(2,5+3,6)+6,2=6,1с+6,2
4) 8,8-3,7+9,7д-2,5д=5,1+7,2д